Hubungan Pola Makan Dengan Kejadian Dispepsia Syndrom di Rumah Sakit An-Nissa Curup - Yevi Ade Hikmah; Darmawansyah Darmawansyah; Delta Aprianti (Jurnal Pakar Kesehatan, 2026)
Dyspepsia syndrome is a common non-communicable disease associated with various risk factors, including dietary patterns. Medical record data from An-Nissa Hospital Curup indicate an increasing trend of dyspepsia cases. Objective: To determine the relationship between dietary patterns and the incidence of dyspepsia syndrome among patients at An-Nissa Hospital Curup.This study employed a quantitative analytic design with a case-control approach. A total of 56 respondents were selected using accidental sampling. Data were analyzed using univariate analysis and bivariate analysis with the Chi-square test.Most respondents were male (62.5%), had basic education (46.4%), were aged over 40 years (57.1%), and were employed (51.8%). The majority had irregular dietary patterns (55.4%) and experienced dyspepsia syndrome (53.6%). Statistical analysis showed a significant relationship between dietary patterns and dyspepsia incidence (p = 0.001). Dietary pattern is significantly associated with dyspepsia syndrome among patients at An-Nissa Hospital Curup. Educational interventions promoting regular eating habits are recommended as preventive measures.